OVERVIEW ON FLOATING DRUG DELIVERY SYSTEM - Niharika, Mirmeera Girish; Krishnamoorthy, Kannan; Akkala, Madhukar (International Journal of Applied Pharmaceutics, 2018)
The principal objective behind the writing of this article on the floating drug delivery system (FDDS) was to systematize the recent literature with the core process of floatation in acquiring gastric retention. The different strategies used in the development of FDDS by constructing the effervescent and noneffervescent type of floating tablets basis of which is buoyancy mechanism. FDDS is a method to deliver the drugs that are active locally with a narrow absorption window in the upper gastrointestinal tract, unstable in the lower intestinal environment, and possess low solubility with higher pH values. The novel methodologies in FDDS include approaches to design a single unit and multiple-unit floating systems, the physiological and formulation variability affecting gastric retention along with the use of recently invented and developed polymers. This review also focuses on various in vitro techniques and in vivo studies in view of performance and application of floating systems. Floating dosage forms can be delivered in conventional forms like tablets, capsules with the addition of suitable ingredients along with the gas generating agent. This review also throws light on different techniques used in developing floating dosage forms along with current and novel advancements.